The effectiveness for therapeutic riding towards autism spectrum disorder children on parental perception - Ng, Sing Ping, 1995-, author 626096 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Project Paper (Sarjana Muda Sains (Pengurusan Ekuin)) - Universiti Teknologi Malaysia, 2019